Sports policies and the New Projectment Economy: a case study of China’s path to Olympic success - Emanuel Leite Junior (Revista Brasileira de Ciências do Esporte)
ABSTRACT This paper focuses on the relationship between China's Olympic success and the New Projectment Economy (NPE). It seeks to demonstrate that China's path to becoming an Olympic superpower is the result of sports policies, through which it is possible to perceive a parallel with the planning that provided the country's economic and technological growth. Based on a literature review on China's Olympic development, this work analyzes the main policies under the theoretical framework of the NPE, in which state planning anticipates the needs of society, resolves contradictions and achieves results in various sectors. China's Olympic success serves as a case study of socialism with Chinese characteristics and the NEP, promoting success not only in the economy, but also in sports.